A novel IGHMBP2 variant and clinical diversity in Vietnamese SMARD1 and CMT2S patients - Tran, Van Khanh; Cao, My Ha; Nguyen, Thi Thanh Hai; Le, Phuong Thi; Tran, Hai Anh; Vu, Dung Chi; Nguyen, Ha Thu; Nguyen, Mai Thi Phương; Bui, The-Hung; Nguyen, Thanh Binh; Ta, Thanh Van; Tran, Thinh Huy (Frontiers in Pediatrics, 2024)
Background: Pathogenic variants in the IGHMBP2 gene are associated with two distinct autosomal recessive neuromuscular disorders: Spinal Muscular Atrophy with Respiratory Distress type 1 (SMARD1; OMIM #604320) and Charcot-Marie-Tooth type 2S (CMT2S; OMIM #616155). SMARD1 is a severe and fatal condition characterized by infantile-onset respiratory distress, diaphragmatic palsy, and distal muscular weakness; while CMT2S follows a milder clinical course, with slowly progressive distal muscle weakness and sensory loss, without manifestations of respiratory disorder. Methods: Whole exome sequencing of the IGHMBP2 gene was performed for eight Vietnamese patients with IGHMBP2-related neuromuscular disorders including five patients with SMARD1, and the others with CMT2S. Results: We identified one novel IGHMBP2 variant c.1574T>C (p.Leu525Pro) in a SMARD1 patient. Besides that, two patients shared the same pathogenic variants (c.1235+3A>G/c.1334A>C) but presented completely different clinical courses: one with SMARD1 who deceased at eight months of age, the other with CMT2S was alive 3 years old without any respiratory distress. Conclusion: This study is the first to report IGHMBP-2-related neuromuscular disorders in Vietnam. A novel IGHMBP2 variant c.1574T>C (p.Leu525Pro) expressing SMARD1 phenotype was detected. The presence of three patients with the same genotype but distinct clinical outcomes suggested the interaction of variants and other factors including relating modified genes in the mechanism of various phenotypes.